Sistem manajemen keamanan informasi dengan standar ISO/IEC 27001 dan ISO/ICE 27002 pada PT Jasa Marga - Soesanto, Edy; Kurniasih, Fadila; Mutiara, Putri; Afifi, Salsabila Taqwaning (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2023)
This study aims to analyze the security management system with ISO/IEC 27001 and 27002 standards at PT Jasa Marga. This study uses a literature search study method with an ISMS approach. Information security management system (ISMS) means a form of process organization based on a business risk approach for planning (Plan), implementation and operation (Execute), monitoring and inspection (Check), and maintenance and improvement or development (Act) of security gossip, ISO/IEC 27000, 27001 and 27002 companies are accepted and adapted using standards. Based on the results of the study, companies that use the ISO/IEC 27001 standard receive ISMS/SMKI professional benefits from third parties who have assessed the security and available evidence. PT Jasa Marga (Persero) Tbk as the first and largest toll road operator in Indonesia continues to improve services for road users, especially in the field of information and technology that continues to increase and develop. It can be concluded that the information security management system at PT. Jasa Marga has complied with the established standards.